Islamic Values-Based Scout Extracurricular Activities and the Development of Students’ Self-Control Ability - Nurhidayani, Nina; Aisyah, Nurul Fitri; Melani, Sri Dewi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This study examines how Islamic values-based scout extracurricular activities contribute to the development of students’ self-control ability at Senior High School 1 Purworejo, Central Java, Indonesia. The study is based on a qualitative field approach involving two scout advisor teachers and fifteen students who actively participated in scout activities. Data were collected through in-depth interviews and observation, then analyzed thematically through data reduction, coding, categorization, and interpretive theme development. The findings show that scout activities function as an experiential space for internalizing Islamic values such as discipline, honesty, responsibility, patience, cooperation, respect, and brotherhood. These values are not only taught verbally, but are practiced through routines, group assignments, ceremonies, mentoring, leadership exercises, and reflective guidance. The study also reveals that students’ self-control develops gradually through repeated experiences of obeying rules, managing time, regulating emotions, completing responsibilities, respecting group decisions, and cooperating with peers. Self-control in this context is not merely a psychological ability, but also a moral and spiritual disposition rooted in Islamic character formation. The study implies that Islamic education should give greater attention to extracurricular activities as practical arenas for strengthening students’ character and self-regulation.